IMPLEMENTASI COACHING KEPADA ADMINISTRATOR DALAM UPAYA MENUMBUHKAN BUDAYA SADAR RISIKO DI RUMAH SAKIT JIWA MUTIARA SUKMA MATARAM - Dianah Afra Faadhilah; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Hospitals, as health service institutions, have a great responsibility to ensure the safety and quality of services to patients. However, many hospitals still lack a culture of awareness regarding the risks of accidents and medical errors. One common issue faced by administrators is noise, incorrect data input, and pressure from tasks assigned by superiors. This leads administrators to seek to be heard regarding their complaints, hence the introduction of coaching, intended so that administrators feel listened to and valued by management through the implementation of coaching. One strategy to foster a culture of risk awareness in hospitals is through the implementation of coaching for administrators. The qualitative approach used in this research has specific characteristics that cannot be addressed with statistical procedures. This research is limited to the objects in the inpatient administration department of a hospital. staff who are considered representative as key informants. Based on the research findings presented above, it can be concluded that the administrators' understanding of coaching is still lacking, with the understanding conveyed by the team leader that the concept of coaching is not much different from conducting briefings and evaluations. A different situation occurs in hospitals generally, where every employee is given understanding and training about coaching to foster a culture of risk awareness while working. This is in line with the opinion of Asbari & Prasetya 2021, which states that the simple process of coaching involves the room head listening and determining whether what the administrator is doing is right or wrong, then providing feedback and paying attention to how things should be done. In light of this research, it is advised that every team leader or unit head should also provide understanding to the administrators, always giving direction and guidance. stay between the unit head and the administrator.